Integral and Anti-Corruption Generation: The Implementation of A Model of Citizenship for Social Projects Based on Religion and School Culture - Mustopa, Azizuddin; Susanti, Siti Saodah (Jurnal Educative: Journal of Educational Studies, 2023)
Corruption has negative impacts on society, including economic, political, and social harm. Indonesia and other nations are plagued by corruption, which requires immediate action. Education, as the foundation of society, is an ideal platform for teaching anti-corruption values from an early age. The purpose of this study is to examine how religious programs and school culture can combat corruption in schools. The study was a descriptive qualitative analysis that involved 23 participants, including the principal, vice principal, PAI teacher, and students. The participants were observed, interviewed, and documented, and the data analysis used Miles-Huberman triangulation. The results show that the implementation of the religious and school culture-based Social Project Citizen model at Sapta Dharma High School, Soreang, is effective in strengthening anti-corruption values among students. The religious program has a clear goal of inculcating anti-corruption values, while the school culture provides concrete examples of actions that support these values. Through the regular implementation of religious projects and the establishment of a school culture that emphasizes integrity, this research positively contributes to the formation of a generation that is less susceptible to corruption and ready to contribute to a clean and just society.Korupsi memiliki dampak negatif terhadap masyarakat, termasuk kerugian ekonomi, politik, dan sosial. Indonesia dan negara-negara lain mengalami masalah korupsi yang membutuhkan penanganan secara serius. Pendidikan, sebagai fondasi masyarakat, merupakan wadah yang ideal untuk mengajarkan nilai-nilai antikorupsi sejak dini. Tujuan dari penelitian ini adalah untuk melihat bagaimana program keagamaan dan budaya sekolah dapat mencegah perilaku korupsi di sekolah. Penelitian ini merupakan penelitian kualitatif deskriptif yang melibatkan 23 partisipan, termasuk kepala sekolah, wakil kepala sekolah, guru PAI, dan siswa. Para partisipan diobservasi, diwawancarai, dan didokumentasikan, dan analisis datanya menggunakan triangulasi Miles-Huberman. Hasil penelitian menunjukkan bahwa implementasi model Social Project Citizen berbasis agama dan budaya sekolah di SMA Sapta Dharma, Soreang, efektif dalam memperkuat nilai-nilai antikorupsi di kalangan siswa. Program keagamaan memiliki tujuan yang jelas untuk menanamkan nilai-nilai antikorupsi, sedangkan budaya sekolah memberikan contoh konkret tindakan yang mendukung nilai-nilai tersebut. Melalui pelaksanaan proyek keagamaan secara rutin dan pembentukan budaya sekolah yang menekankan integritas, penelitian ini berkontribusi positif terhadap pembentukan generasi yang tidak rentan terhadap korupsi dan siap untuk berkontribusi pada masyarakat yang bersih dan adil.